Pre-service teachers’ demographics, cultural competence, and culturally responsive teaching practices - Z. Andal, Edilberto; E. Panergayo, Albert Andry (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study examines the influence of cultural competence (CC) on culturally responsive teaching (CRT) practices among pre-service teachers (PSTs) in a state university in Laguna, Philippines. Despite the emphasis on education, the impact of cultural awareness, knowledge, and skills on CRT remains underexplored. Using a cross-sectional quantitative research design, data from 633 PSTs were collected through a validated web-based survey. Multiple regression analysis showed that cultural knowledge (B=0.373, p<0.05) and cultural skills (B=0.511, p<0.05) significantly predict CRT practices, while cultural awareness (B=0.003, p>0.05) does not. Demographic factors such as age, gender, and year level do not moderate this relationship. These findings highlight the need for prioritizing cultural knowledge and skills in teacher education curricula. Institutions should integrate structured training to equip PSTs for diverse classrooms. Future research should explore the long-term effects of these competencies in an actual teaching environment and assess targeted training interventions. Strengthening CC through curriculum enhancement can better prepare educators to meet the challenges of an increasingly diverse educational landscape.